Posterior Cortical Atrophy Presenting with Superior Arcuate Field Defect. (31st August 2015) - Wan, Sue Ling; Bukowska, Danuta M.; Ford, Stephen; Chen, Fred K.
Abstract : An 80-year-old female with reading difficulty presented with progressive arcuate field defect despite low intraocular pressure. Over a 5-year period, the field defect evolved into an incongruous homonymous hemianopia and the repeated neuroimaging revealed progressive posterior cortical atrophy. Further neuropsychiatric assessment demonstrated symptoms and signs consistent with Benson's syndrome.